Breaking the Malaysian political media dichotomy: A case for citizen’s media - Mohamed, Shafizan (International Academic Research, 2017)
The alternative media is a significant component in Malaysian political life. Because of the Government’s control of the mainstream media, the alternative media becomes the source Malaysians refer to for other political news. George (2006) explained that the Malaysian alternative media is politically contentious in the sense that it is focused on offering news and information that specifically challenges the credibility of the state-controlled mainstream media. Studies on the Malaysian media often reinforced this dichotomy by referring to all other non-government political media as the alternative media (Steele, 2009). As such, the alternative media has often been taken as a blanket term covering all forms of non-mainstream media and this undermines the complexities and specificities of the many kinds of democratic media practices. The media choice is always “either-or”. This binary becomes problematic when trying to understand other forms of media, especially the social media that are owned by individuals and used for many purposes that go beyond subversive politics. Thus, this paper unpacks the problematic application and categorisation of this dichotomy while offering a more inclusive approach through the theoretical ideas of Citizen’s Media.